Analisis Peningkatan Kinerja Guru Melalui Reward di Sekolah Dasar Islam Raudhah BSD - Siti Halimah; Puput Roniansyah; Muchamad Zainal Muttaqin; Hasyim Asy’ari (Indonesian Journal of Islamic Educational Management, 2023)
This study aims to analyze the increase in teacher performance through rewards, this research uses qualitative research methods based on descriptive studies, data collection techniques for research using observation techniques, interviews, and document analysis. Teacher performance can be improved through the provision of rewards, at Raudhah Islamic Elementary School the rewards are in the form of Masters and Umrah scholarships, these rewards are given to employees who have served as permanent employees of the Foundation and are based on the selection results of the management team. Assessment of reward from three aspects of tenure, position, performance appraisal consists of performance, personality attitude and additional positions such as homeroom teacher and deputy principal of the school.